Penerapan Kitab Kisrah Durar Al Lawāmi’ Dalam Pembelajaran Nahwu di Madrasah Diniyah Al Amin Bulusari - Misbahuddin Naufal; Nurrokhmatulloh Nurrokhmatulloh; Syaifullah Syaifullah (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
The literature study analysis technique aims to increase understanding of the application of the book nadhom Kisrah Durar Al Lawami', based on a spiral approach in developing the learning of nahwu science. The science of nahwu is a grammar that has a central role in understanding sources such as the Qur'an and Hadith and classical books. This study uses a descriptive qualitative method with a field research. The results of this study analyze data about the learning of nahwu science in the book of nadhom Kisrah Durar Al Lawami' by Syeikh Khozin Mansur, whose books have been used in Islamic boarding schools founded by him for decades, This research identifies two important research findings related to the application of the book of Kisrah Durar Al Lawami' and becomes a great hope for students to absorb knowledge comprehensively, So that it can identify some weaknesses that occur in students, because basically spiral tightening is the concept of learning repetition in stages that start from easy to difficult. In order to accommodate the diverse needs of students. A wider scope and a more in-depth analysis are recommended to enrich the scientific treasures about the effectiveness of the implementation of classical books in improving the learning of nahwu knowledge in the Diniyah madrasah environment.